Tropospheric scintillation prediction models for a high elevation angle based on measured data from a tropical region - Abdul Rahim, Nadirah; Islam, Md. Rafiqul; J.S., Mandeep; Dao, Hassan; Nasr, Saad Osman Bashir (Pergamon, 2013)
The recent rapid evolution of new satellite services, including VSAT for internet access, LAN interconnection and multimedia applications, has triggered an increasing demand for bandwidth usage by satellite communications. However, these systems are susceptible to propagation effects that become significant as the frequency increases. Scintillation is the rapid signal fluctuation of the amplitude and phase of a radio wave, which is significant in tropical climates. This paper presents the analysis of the tropospheric scintillation data for satellite to Earth links at the Ku-band. Twelve months of data (January-December 2011) were collected and analyzed to evaluate the effect of tropospheric scintillation. Statistics were then further analyzed to inspect the seasonal, worst-month, diurnal and rain-induced scintillation effects. By employing the measured scintillation data, a modification of the Karasawa model for scintillation fades and enhancements is proposed based on data measured in Malaysia.